1994
DOI: 10.1159/000276631
|View full text |Cite
|
Sign up to set email alerts
|

Bony Anatomy of the Anterior Epitympanic Space

Abstract: The anatomy of the anterior epitympanic space is complex and relatively unfamiliar to the surgeon. The size of the space is unpredictable. From the surgeon’s perspective, we studied the bony anatomy of the anterior epitympanic space in 35 cadavers. There was an impressive variability of bony openness into the anterior mesotympanum; the openness was bilaterally symmetrical. As a potential auxiliary ventilation route for the epitympanum of the chronic otitis patient, each specimen was found to have sufficient ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…To prevent this complication, it is important to establish a ventilation route from the anterior mesotympanum through the anterior epitympanic space into the epitympanum, as pointed out by Todd et al (1994). Unfortunately, many patients with acquired cholesteatoma suffer from persistent eustachian tube dysfunction, which may lead to the development of recurrent cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent this complication, it is important to establish a ventilation route from the anterior mesotympanum through the anterior epitympanic space into the epitympanum, as pointed out by Todd et al (1994). Unfortunately, many patients with acquired cholesteatoma suffer from persistent eustachian tube dysfunction, which may lead to the development of recurrent cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent cholesteatoma developing from a retraction pocket has been found to be a frequent complication after a canal wall-up mastoidectomy (Sade, 1993) but the current study revealed this condition was also a problem after canal wall-down mastoidectomy with simultaneous tympanoplasty. To prevent this complication, it is important to establish a ventilation route from the anterior mesotympanum through the anterior epitympanic space into the epitympanum, as pointed out by Todd et al (1994). Unfortunately, many patients with acquired cholesteatoma suffer from persistent eustachian tube dysfunction, which may lead to the development of recurrent cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…Han sido fundamentales para esta redacción, los trabajos clásicos de Chatellier y Lemoine (1946) [7], explicando la constitución del diafragma inter-ático-timpánico; el de Proctor (1964) [2] sobre el desarrollo embriológico del oído medio y su significado quirúrgico y la descripción inicial que realizan Wigand y Trillsch (1973) [1], de la anatomía del seno epitimpánico. Los estudios de disección anatómica e histológica de Hoshino (1988) [5], Yamasoba et al (1990) [8], Caprio et al (1994) [9] y Djeric et al (1985) [10], junto a la perspectiva quirúrgica de Todd et al (1994) [3] y la endoscópica de Li et al (2018) [11], nos han permitido comprender la variabilidad estructural del REA y su relación con el pliegue mucoso del músculo tensor del tímpano. Pero quienes presentan el mayor número de publicaciones, siendo citados por la mayoría de los autores, son el grupo de Palva et al [4,12], que a través de la histología del hueso temporal describen pormenorizadamente este espacio, sus rutas de ventilación y la influencia de los procesos patológicos.…”
Section: Resultsunclassified
“…Descripción anatómica del REA Djeric y Savic, (1985) [10] identificaron el REA en 55 de 100 temporales, con unas dimensiones en altura, de 2,5 a 5,5 mm (media de 2,3 mm); en anchura de 2,5 a 5,5 mm (media 3 mm) y con un diámetro anteroposterior de 2 a 7,5 mm (media de 6,2 mm). Para simplificar la descripción de este espacio, vamos a considerarlo como un cubo de seis paredes [3]. La pared posterior, situada inmediatamente por delante de la cabeza del martillo, está constituida por una lamela ósea, a la que hemos denominado cog (que significa rueda dentada), placa ósea del ático anterior o placa transversa maleolar.…”
Section: Desarrollo Embriológico Del Reaunclassified
See 1 more Smart Citation